2013
DOI: 10.3389/fpls.2013.00125
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Phosphofructokinase Gene Family in Rice and Its Expression Under Oxygen Deficiency Stress

Abstract: Plants possess two types of phosphofructokinase proteins for phosphorylation of fructose-6-phosphate, the ATP-dependent phosphofructokinase (PFK) and the pyrophosphate-(PPi) dependent pyrophosphate-fructose-6-phosphate-phosphotransferase (PFP). During oxygen deficiency ATP levels in rice seedlings are severely reduced, and it is hypothesized that PPi is used as an alternative energy source for the phosphorylation of fructose-6-phosphate during glycolysis. In this study, we analyzed the expression of 15 phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 78 publications
(126 reference statements)
0
40
0
Order By: Relevance
“…In "Granny Smith" apples, PFK is highly responsive to subtle changes in oxygen concentration (Cukrov et al, 2016), and, similarly to SuSy, uses PPi instead of ATP to save energy (Bailey-Serres et al, 2012). PFK most likely represents a key element for re-setting carbon metabolism under oxygen deficiency through an induction of the glycolytic pathway in rice (Mustroph et al, 2013). Both PFK and pyruvate kinase (PK) are highly and rapidly responsive to subtle changes of oxygen concentrations in apple tissues (Brizzolara et al, 2019).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…In "Granny Smith" apples, PFK is highly responsive to subtle changes in oxygen concentration (Cukrov et al, 2016), and, similarly to SuSy, uses PPi instead of ATP to save energy (Bailey-Serres et al, 2012). PFK most likely represents a key element for re-setting carbon metabolism under oxygen deficiency through an induction of the glycolytic pathway in rice (Mustroph et al, 2013). Both PFK and pyruvate kinase (PK) are highly and rapidly responsive to subtle changes of oxygen concentrations in apple tissues (Brizzolara et al, 2019).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…The hexokinase (HK) activity was assayed according to Schaffer and Petreikov [75]. The phosphofructokinase (PFK) activity was measured according to Mustroph et al [76]. The pyruvate kinase (PK) was determined according to Schweizer and Erismann [77].…”
Section: Transcriptome Assembly and Gene Functional Annotationmentioning
confidence: 99%
“…ATP-PFKs are found to be a large gene family: at least seven genes encoding ATP-PFK were found in Arabidopsis (Mustroph et al 2007) and ten were found from rice (Mustroph et al 2013). PFP genes are of a smaller gene family.…”
Section: S Gfpmentioning
confidence: 99%